Bio‐Based Cycloalkanes: The Missing Link to High‐Performance Sustainable Jet Fuels. Issue 22 (25th September 2020) - Muldoon, Jake A.; Harvey, Benjamin G.
Abstract: The development of sustainable energy solutions that reduce global carbon emissions, while maintaining high living standards, is one of the grand challenges of the current century. Transportation fuels are critical to economic development, globalization, and the advancement of society. Although ground vehicles and small aircraft are beginning a slow transition toward electric propulsion with energy sourced from solar radiation or wind, the extreme power requirements of jet aircraft require a more concentrated source of energy that is conveniently provided by liquid hydrocarbon fuels. This Review describes recent efforts to develop efficient routes for the conversion of crude biomass sources (e. g., lignocellulose) to cycloalkanes. These cycloalkanes impart advantageous properties to jet fuels, including increased density, higher volumetric heat of combustion, and enhanced operability. The combination of bio‐based cycloalkanes and synthetic paraffinic kerosenes allows for the preparation of 100 % bio‐based fuels that can outperform conventional petroleum‐based fuels. In this Review methods are described that convert biomass‐derived small molecules, including furfural, furfuryl alcohol, 5‐hydroxymethylfurfural, cyclic ketones, phenolics, acyclic ketones, cyclic alcohols, furans, esters, and alkenes to high‐density cycloalkanes. In addition to describing the chemical transformations and catalysts that have been developed to efficiently produce various cycloalkanes, this Review includes summaries of key fuel properties, which highlight the ability to generate fuels with customized performance metrics. This work is intended to inspire other researchers to study the conversion of sustainable feedstocks to full‐performance aviation fuels. An acceleration of this research is critical to reducing the carbon footprint of commercial and military aviation on a timescale that will help blunt the impacts of global warming. Abstract : Out with the old carbon and in with the new : Conventional jet fuel is tough to beat, but recent work on the conversion of bio‐based feedstocks to cycloalkanes allows for the production of sustainable jet fuels that can outperform petroleum. This Review summarizes recent progress on the catalytic conversion of renewable platform chemicals to high‐density aviation fuels. These new fuels offer enhanced range and cleaner combustion while reducing net greenhouse gas emissions.